2019
DOI: 10.3847/1538-3881/aafc31
|View full text |Cite
|
Sign up to set email alerts
|

Apsidal Motion and Absolute Parameters of 21 Early-type Small Magellanic Cloud Eccentric Eclipsing Binaries

Abstract: We present the apsidal motion as well as the light curve analyses of 21 eccentric eclipsing binaries located in the Small Magellanic Cloud. Most of these systems have never been studied before, hence their orbital and physical properties as well as the apsidal motion parameters are given here for the first time. All the systems are of early spectral type, having the orbital periods up to 4 days. The apsidal motion periods were derived to be from 7.2 to 200 years (OGLE-SMC-ECL-2194 having the shortest apsidal p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The second method is to simultaneously fit all the observational data with a code allowing for the argument of periastron to vary by a linear rate of change in time, thus directly handling apsidal motion rate. Such an analysis has been applied using the PHOEBE code (an open-source project, see [17,18]) in [16,19].…”
Section: In An Eclipsing Binarymentioning
confidence: 99%
“…The second method is to simultaneously fit all the observational data with a code allowing for the argument of periastron to vary by a linear rate of change in time, thus directly handling apsidal motion rate. Such an analysis has been applied using the PHOEBE code (an open-source project, see [17,18]) in [16,19].…”
Section: In An Eclipsing Binarymentioning
confidence: 99%
“…It is worth noting that the light curve taken with the filter centred on the He ii λ 4686 line is in excellent agreement with the best-fit c 2 -band curve, and does not reveal any strange behaviour due to the phase-dependent He ii λ 4686 emission. The light curves of eclipsing binaries are also quite sensitive to apsidal motion and are frequently used to establish the presence of this phenomenon (e.g., Zasche & Wolf 2019). In the case of HD 152 248, the eclipses were discovered and confirmed well after the discovery of the SB2 nature of the system (Mayer et al 1992).…”
Section: Light Curve Analysismentioning
confidence: 99%
“…Interestingly, some previous studies reported evidence of a secular variation of the argument of periastron ω (Sana et al 2001;Nesslinger et al 2006;Mayer et al 2008). These properties make HD 152 248 an ideal target for the study of apsidal motion (Schmitt et al 2016;Rauw et al 2016;Zasche & Wolf 2019). Apsidal motion consists in a slow precession of the line of apsides in an eccentric binary and stems from the non-spherical shape of the gravitational field of stars in close binaries (Schmitt et al 2016, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In our case we have almost 20-year long coverage, which for orbital periods of 4-5 days, can give a very high precision in the determination of the time-related parameters, like period and times of minima. This in turn let us detect and measure the precession of the line of apsides, which is a very common phenomena in massive binary systems (Garcia et al 2014;Pablo et al 2015;Rauw et al 2016;Zasche & Wolf 2019).…”
Section: Apsidal Motionmentioning
confidence: 99%